Comparative evaluation of conventional and ultrasound assisted tube cystotomy for obstructive urolithiasis in cattle - SUDRIK, P P; SURYAWANSHI, R V; ULEMALE, A H; AHER, V D; AGIVALE, S M; DHAIGUDE, V S (The Indian Journal of Animal Sciences, 2024)
The aim of this study was to evaluate the efficacy of conventional and ultrasound assisted tube cystotomy techniques for obstructive urolithiasis in 12 cattle by allowing two groups. Group-I, animals were subjected to conventional tube cystotomy, whereas in group- II, ultrasound assisted tube cystotomy was performed using Foley’s catheter under deep sedation with xylazine hydrochloride and local infiltration anaesthesia. Clinically, all animals showed urethral pulsation, dribbling of urine, futile attempts, bellowing, congested mucous membrane, sunken eyes, dry muzzle and teeth grinding. Non-significant changes were observed in haematological and biochemical values, however neutrophilia and alkaline pH of urine was prominent. Ultrasound assisted tube cystotomy technique consumed less time (40.00±1.29 min) with small incision and minimal bleeding as compared to conventional tube cystotomy.